¿Influencias occidentales en el Mapa Quinatzin? - Lesbre, Patrick (Revista Española de Antropología Americana, 2008)
We will try to find possible occidental influences in the Quinatzin Map, an acolhua early colonial codex (Central Valley of Mexico). We will focus first on a possible westernisation of drawing or pictographic writing: some pictorial techniques (perspective, volume and depth, use of colours), but also various naturalistic elements instead of pictographic (plants, toponyms, bodies etc.). We will indicate some phoneticism, an atypical use of calendar and some thematic omissions. This poses the difficult problem of distinguish between westernisation and regional styles.Nous chercherons de possibles influences occidentales dans la Mappe Quinatzin, codex acolhua (Vallée centrale de Mexico) de date coloniale précoce. Nous nous centrerons d’abord sur une possible occidentalisation du dessin ou de l’écriture pictographique: certaines techniques picturales (perspective, volume et profondeur, emploi des couleurs), mais aussi plusieurs éléments naturalistes et non pictographiques (elements végétaux, toponymes, corps etc.). Nous signalerons un certain phonétisme, un usage atypique du calendrier et certaines omissions thématiques. Ce qui pose en réalité le difficile problème de distinguer entre occidentalisation et styles régionaux.
Keywords: Aztec codex; Aztec culture; Ethnohistory; Cultural métissage; Tezcoco; Codex aztèques; Culture aztèque; Ethnohistoire; Métissage culturel